الفكر الأصولي عند الإمام أبي الحسن الأشعري (ت 324هـ): دراسة تحليلية - سلهب، بلال بركات سليمان (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This thesis is concerned with an important, yet understudied, aspect of Abu Ḥasan al-Ash'ari's (260-324 H./874-936 C.E.) intellectual and scholarly legacy, namely the aspect relating to subjects of Islamic legal theory (uṣul al-fiqh). Hardly do we have a systematic and comprehensive view of the epistemological and methodological components constituting his jurisprudential thought in respect of the Shari'ah rulings and their grounds, legal proofs and the methods of derivation of rulings there-from, and the relationship among the proof sources (adillah) of the Shari'ah. We do not possess such a way as would allow us to consider it representative of al-Ash'ari's legal thought as an integrated system. The reason for that is that al-Ash'ari's views on matters of Islamic legal theory have not been studied on their own independently, but rather were mostly invoked either as merely secondary issues in the study of theological subjects, or dealt with in the framework of studies on usuli thought in its later stages as reflected in the works of al-Baqillani, Qaḍi ʻAbd al-Jabbar, al-Juwayni, and their likes. Likewise, there is no comprehensive independent study combining thoroughness in presenting al-Ash'ari's usuli opinions with analysis and restructuring so as to arrive at an integrated picture of the different components of his usuli thought, which can be seen as a coherent structure. In this study, the researcher relied primarily upon an inductive methodology to explore, collect, and thoroughly investigate al-Ash'ari's usuli opinions and sayings from their most probable sources, initially relying upon what is available of al-Ash'ari's writings, and then whatever is closest. Then the researcher utilized an analytical methodology to analyze and break down al-Ash'ari's usuli opinions, and then to study them and their premises before piecing them together in the context of the reality and scientific environment in which those opinions were voiced. Then they were evaluated in light of the usuli methodology that al-Ash'ari himself espoused, all in order to arrive at the general characteristics of usuli thought according to al-Ash'ari. The researcher concluded with a set of findings, most important of which are: al-Ash'ari's Usul al-Fiqh was influenced by the science of Kalam, and al-Ash'ari was a proponent of an independent methodology of ijtihad in Usul al-Fiqh. Furthermore, al-Ash'ari abstained from passing judgment in some usuli questions, and he differentiated between fundamental and secondary elements in ijtihad.